Juiz de paz e cultura política no início do oitocentos (Província do Espírito Santo, 1827-1842) - Motta, Kátia Sausen da (2013)
On the first decades of the XIXth century the guiding principles of political association and citizenship were constructed and designed, among which it contrasts the Justice of Peace. The Constitutional Charter of 1824 ensured the legal basis of that institution and also established its elective condition, although the complete legal regulation of its functions and election was delegated to the National Assembly. During the decades of 1820 and 1830 in Brazil several laws were created regarding the institution’s regulation, like the Leis Ordinárias de 1827/1828 and the Código de Processo. This dissertation investigates a time during which the Brazilian political members first thought the new elective magistrate and also how it functioned in the Province of Espírito Santo.